TA’WĪL DAN HERMENEUTIKA SEBUAH PERBANDINGAN - Said, Abdurrahim (LPPI Universitas Al-Qolam Malang, 2015)
Text Comprehension requires theory as a tool for understanding. Theories are needed to avoid errors in the text understanding. In Islam, a theory to understand the sacred text recognized as Tafsir and ta'wil. Tafsir and ta'wil compiled by muslim scholars as an attempt to understand the content of Al-Quran as the guidance of Muslims life. In the tradition of Western philosophy, such theory known as hermeneutics. Hermeneutic is a philosophy as well as a method of understanding the text. Some of it experts are, Paul Ricoeur, Scheleirmecher, and Jurgen Habermas. Each one had a religious opinion and gave color to the discourse of hermeneutics.Hermeneutics is often misunderstood as synonymous with tafsir or ta'wil in the Islamic tradition. It is certainly misleading because there are fundamental differences between hermeneutics and ta'wil or tafsir. The differences mainly lie in the source of epistemology, the principle of relativity-absolute, as well as Skeptic and speculative basis.Keywords: interpretation, hermeneutics, comparative